Guerrilla Resistance: Sitti Nurbaya and Balai Pustaka’s Censorship - Adek, Muhammad; Pangesti, Nesa Riska; Dewi, Siska Miga; Putra , It Fernando (BAHASTRA, 2024)
Censorship, a tool of cultural hegemony often employed by colonizers, was practiced by the Dutch colonials in the Dutch East Indies through the people's reading commission or Balai Pustaka, as evidenced in the Nota Rinkes, which prohibited literary works with subversive political content, religious sentiments, and immoral themes. This study explores the content of the novel Sitti Nurbaya, a prominent publication from Balai Pustaka, using a postcolonial approach and Gramsci's theory of cultural hegemony as analytical tools. The findings reveal that Sitti Nurbaya contains elements of progressive politics through the Belasting riots, intense religious sentiment in defense of Adat teachings, and characters with flawed morals. Consequently, it is concluded that Sitti Nurbaya managed to circumvent Balai Pustaka's censorship and functioned as an organic intellectual, sparking anti-colonial awareness.